Students' Views of Teacher’s Feedback in L2 Writing Class - Ali, Helena; Prasatyo, Bayu Andika; Sari, Farnia (Dialectical Literature and Educational Journal, 2023)
The objective of this study was to scrutinize the nature of corrective feedback delivered by instructors in English as a Foreign Language (EFL) classrooms and to delve into the perspectives of students who received such feedback from their educators. The study seeks to explore the diverse forms of corrective feedback utilized by instructors to address flaws or errors in students' writing practices, while also examining students' perceptions of this feedback subsequent to the correction process. The research was conducted at a private university situated in Bekasi, employing a qualitative descriptive approach. Data collection encompassed the distribution of questionnaires and the conduction of interviews. This study reveals that instructors furnish students with five distinct types of feedback. The results indicate that Lexical Feedback is consistently provided to all students, closely followed by Grammar Feedback. Additionally, a majority of students frequently receive Structural Feedback. Insights from the interviews highlight that a substantial number of students exhibit a favorable disposition towards the various forms of corrective feedback employed by the instructors. Moreover, this research underscores the imperative of integrating corrective feedback into the English language instruction for students learning English as a foreign language (EFL).